An Evaluation of Violent Terrorist Groups, Conflict and Development in the Sahel-Sahara Region - Saka, Moshood (Acta Universitatis Danubius. Juridica, 2024)
Sahel-Sahara region has been enduring series of conflicts which range from varying degrees with detrimental impacts on the lives of millions of inhabitants living in the region. While many studies have strongly affirmed this assertion, the emerging states are divided in terms of secular religion, pastoralist, farmer and ethnicity which resulted in persistent conflicts. These elements have devastating effects on the socio-economic development, natural cohesion, peace and nation building in the region. The aim of this study, therefore, was to examine the tide of terrorism and the attendant effects in the region. Using qualitative research methods, the study explores the background of the multidimensional crisis and analyse the violent terrorist groups, communal conflicts, causes of the crisis, development crisis and measures implemented by various international organisations to stem the tide for nation building. Primary and secondary sources were utilised to provide deeper insights and support the analysis. The findings reveal that lack of democratic institution in the region is the major causes of the crisis measures and efforts to eradicate insecurity are significant processes in this study. The study concludes that multifaceted issues of insecurity, violent, terrorism and communal conflicts in the region are evidence that the implementation of democratic measures in the region has not yielded progress